Cultivation of Oyster Mushroom (Pleurotus florida) on Sawdust - Negi, RS; Singh, Santosh; Debnath, Haripada (Mushroom Research, 2022)
The study was conducted at Department of Rural Technology, HNB Garhwal University Srinagar Garhwal, Uttarakhand during 2018-2019 for cultivation of Pleurotus species (Pleurotus florida) on three different treatments of Sawdust i.e. T1 (Sawdust), T2 (Sawdust 70% +Rice bran 30% ) and T3 (Sawdust, 80% + 20% rice bran. The study was examined for spawn running (mycelia development), pinhead formation and fruit body formation and yield production. Among all the treatments T2 (Sawdust 70% +Rice bran 30%) was found most favourable for oyster mushroom (Fleurotus florida) cultivation.